Peran Persepsi Harga Dalam Memoderasi Hubungan Kualitas Produk terhadap Keputusan Pembelian Air Minum Dalam Kemasan (AMDK) Dikalangan Generasi Z: Bukti dari Kajian Systematic Literature Review - Muhamad Ramdhan; Dede Djuniardi (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
Bottled drinking water (AMDK) has become a basic need for people in Indonesia. Consumers when choosing AMDK consider various factors, including product quality and price. Many companies that produce bottled drinking water have to compete to get their products chosen by consumers. Generation Z, when deciding to purchase a product, looks at various aspects such as product quality and price as factors to consider. So a review is needed journal papers  which discusses product quality on purchasing decisions with price perceptions as a moderation that strengthens this relationship. Method used in this research are Systematic Literature Review (SLR), which focuses on journal articles published from 2019 to 2023. This study sets three research questions (Research Questions, RQ). The focus of this research is on bottled drinking water producers in the hope that it can help understand consumer behavior and implement appropriate strategies to increase product sales.